SURFACE HARDENING CHARACTERIZATION OF TRANSMISSION GEARS - Rifky Ismail; . Jamari; M. Tauviqirrahman; . Sugiyanto; Trias Andromeda (Prosiding SNST Fakultas Teknik, 2011)
This paper is presented to compare the transmission gear products from SME (UKM gear) and national scale manufacturer (OEM gear) especially on the surface hardening characterization. Both gears were heat treated with different methods. The gear product of SME was heat treated by pack carburizing and quenching whereas the OEM gear was predicted to be heat treated using induction heating with high frequency. The surface hardening characterization was conducted by investigating the hardening thickness, the hardness number and the microstructure observation on the gear surfaces. The result of the hardening thickness investigation reveals a distinction on the depth of hardening penetration. The heat treatment using long interval pack carburizing of UKM gear produces a deeper penetration and the higher hardness number on the gear surface whereas the OEM gear has a thin hardness penetration and lower hardness number. The microstructure of the both gears depicts the different types of phase. The SME gear shows the present of the carbon infiltration on the martensitic phase structure boundary whereas the OEM gear exhibits lower bainite phase on the gear surface. With this condition the OEM gear is predicted to behave a better contact stress distribution during operation. Keywords: gear, heat treatment, surface hardening, microstructure